Elastic Bands During Half-Squats as A Re-Warm-Up Strategy for Youth Soccer Players' Performance. - Sanchez-Sanchez, Javier; Clemente, Filipe Manuel; Ramirez-Campillo, Rodrigo; Rodríguez-Fernández, Alejandro (Journal of Sports Science & Medicine, 2024)
The study aimed to assess the immediate effects of re-warm-up strategies using half-squats with elastic looped bands on the performance of youth soccer players. A cross-over study design with repeated measures was implemented in field youth male soccer players (n = 20, age 15.7 ± 0.8 years). Following the first 45-min of match play, players were subjected to one of four re-warm-up (Re-w) interventions of equal duration: no Re-w (PAS), half-squat without elastic looped bands (SQ), half-squat with bands placed on the thighs (SQT), and half-squat with bands placed on the lower legs (SQL). These interventions were compared against a control condition (CON). The Re-w protocols were initiated 10-min after half-time, and players' performance was evaluated through vertical and horizontal jump tests, 20-m linear sprint, and T-agility test. Statistical analysis using ANOVA revealed that the SQT and SQL interventions significantly improved (p < 0.001) several performance metrics compared to the PAS and SQ conditions. These improvements were observed in squat jumps, unilateral squat jumps (both dominant and non-dominant legs), countermovement jumps, horizontal jumps, triple horizontal jumps, the 20-m linear sprint, and T-agility performance. In conclusion, SQT and SQL are equally effective to enhance performance as Re-w strategies after the 1st-half of a soccer match. However, the lack of physiological data and 2nd-half assessments suggests the need for further research to confirm the persistence of these effects.